Black carbon traces of human activities in stalagmites from Turkey. (November 2020) - Koç, Koray; Koşun, Erdal; Cheng, Hai; Demirtaş, Ferdi; Lawrence Edwards, R.; Fleitmann, Dominik
Abstract: Speleothems are recognized as sensitive recorders of climatic fluctuations in the past and provide precisely dated and highly resolved environmental records. However, their potential as an archaeological archive is not fully acknowledged yet. Here we present several stalagmites containing soot and charcoal layers from various caves in Turkey and provide evidence that these black carbon layers are directly related to human activity. The archaeological artefacts found in Tabak and Kocain caves in SW Turkey support the linkage between soot and charcoal layers existence and human activity in the caves. For this study, we focus on stalagmites from Tabak and Kocain cave. To explore the age and nature of the soot and charcoal layers within stalagmites Ta-9, Ta-10 and Ko-1, Uranium series dating, scanning electron microscope (SEM) and thin section analyses were performed. The episodic soot and charcoal deposition in stalagmites Ta-9 and Ta-10 occurred between 7424 ± 225 yr BP and 6670 ± 218 yr BP while the soot and charcoal layers in stalagmite Ko-1 formed between 2830 ± 189 yr BP and 470 ± 56 yr BP. In combination with the archaeological inventory in Tabak Cave, the soot and charcoal layers within stalagmites Ta-9 and Ta-10 show that the cave was used repeatedly as a burial site during Chalcolithic period. In Kocain Cave was also used repeatedly between the Iron Age and Medieval Period, most likely for ritual activities and for providing animals with water from a small spring in the entrance to the cave. The soot and charcoal layers within stalagmites from Turkey prove that speleothems are also important as archaeological archives. Highlights: We investigated potential of speleothems as archaeological archives. U–Th dating analyses were performed on three stalagmites collected from SW Turkey. Several stalagmites from Turkey containing soot and charcoal layers are the records of human activity in and around the caves. Stalagmites have great potential to illuminate the history of the region.